Rekayasa Budidaya Melon Hidroponik dalam Greenhouse untuk Meningkatkan Pendapatan Masyarakat Desa Purwojati - Murdiantoro, Randi Adzin; Nur, Ivan Akmal; Isnawati, Anggun Fitrian; Afandi, Mas Aly; Rumestri, Agatha Dinarah Sri; Purwanti, Eri Nanda Dewi; Nurmeilinda, Kharisma; Anjani, Mia; Saputra, Sahrul; Arsiandro, Fadzly Haris; Nurkholis, Rizki; Prasetio, Angga Ari; Utari, Tria; Fadillah, Siti; Sutarmin, Sutarmin (CV. ITTC INDONESIA, 2024)
Agriculture is still the main sector in rural economy in Indonesia, including in Purwojati Village. This village is one of the extreme poor areas in Purwojati Subdistrict, Kabupaten Banyumas, where most of the area is dry land. Banyumas whose area is mostly dry land. Based on this condition, it is necessary to modify the technology on commodities in the based on these conditions, it is necessary to modify the existing commodities in the area, namely hydroponic melon cultivation engineering in greenhouses. The purpose of this activity is to increase cultivation productivity to increase community income. The results of the use of greenhouses in the use of greenhouses in golden melon cultivation in Purwojati Village increases productivity up to 4-5 times per year for 1 unit of greenhouse. harvest per year for 1 greenhouse unit, better fruit quality, and increased community knowledge in the field of hydroponic melon cultivation. better fruit quality, and increased community knowledge in the field of business management and modern agriculture. This has the potential to increase community income significantly, thus supporting economic empowerment and income significantly, thus supporting economic empowerment and improving welfare of farmers in the area.